Health‐related quality of life following treatment for extremity soft tissue sarcoma. Issue 7 (16th September 2016) - Davidson, Darin; Barr, Ronald D.; Riad, Soha; Griffin, Anthony M.; Chung, Peter W.; Catton, Charles N.; O'Sullivan, Brian; Ferguson, Peter C.; Davis, Aileen M.; Wunder, Jay S.
Abstract : Background and Objectives: The primary objective of this study was to estimate the change in health‐related quality of life (HRQL) 1 year following treatment for extremity soft tissue sarcoma (STS), measured by the EQ‐5D. Secondary objectives included determining clinical variables associated with HRQL at 1 year, estimating the proportion with a clinically important difference (CID) in HRQL, and evaluating variability within EQ‐5D domains. Methods: Patients over the age of 16 years, treated for a localized extremity STS, were included. The EQ‐5D change score from pre‐treatment to 1‐year follow‐up was determined. The association of clinical variables with EQ‐5D scores was estimated using a linear regression model. The proportion of patients with a CID in HRQL score was determined. A vector analysis of the EQ‐5D domains was undertaken. Results: The mean EQ‐5D change score was 0.02. Age, sex, disease status, and initial EQ‐5D score were associated with EQ‐5D score at 1 year. There was a CID improvement in 32% and a deterioration in 24%. The anxiety and depression domain demonstrated the most change between baseline and 1 year after treatment. Conclusion: Most patients maintain a high level of HRQL following treatment for extremity STS. J. Surg. Oncol. 2016;114:821–827 . © 2016 2016 Wiley Periodicals, Inc.